Thermal ocular and adnexal burn from a domestic wooden fire: a preventable cause of vision-threatening injury - Yadav, Niraj K.; Singh, Swati; Abbasi, Sadaf; Singhal, Semone; Sajimon, Shweta; Ragunath, Reshma (International Journal of Research in Medical Sciences, 2026)
Thermal ocular injuries represent true ophthalmic emergencies that can result in significant morbidity if not managed promptly. Burns caused by domestic wooden fires, although uncommon, remain a preventable source of ocular trauma, particularly in rural or resource-limited environments where open-fire cooking is common. We report the case of a 38-year-old woman who sustained an accidental ocular and periocular thermal burn when her infant inadvertently struck her left eye with a burning wooden stick while she was cooking on a traditional chulha. On examination, she exhibited a partial-thickness burn of the lower eyelid and infraorbital skin, singeing of eyelashes, and deposition of carbon particles within the inferior conjunctival fornix. The cornea showed a 4 × 3 mm epithelial defect with fluorescein uptake but without stromal involvement. Immediate and copious irrigation, followed by mechanical removal of carbon debris and initiation of topical antibiotic-steroid therapy with lubricants, led to rapid improvement. By the three-week follow-up, the patient achieved complete epithelial healing, resolution of inflammation, and restoration of 6/6 visual acuity, without cicatricial or corneal complications. This case underscores that ocular and adnexal burns from domestic wooden fires are rare yet entirely preventable. Early recognition, prompt irrigation, and meticulous debridement are crucial to preventing vision-threatening sequelae. Increased public awareness, patient education, and fire safety measures remain essential to reducing the burden of preventable domestic ocular injuries.